Visser_data_vocal_foragers_silent_crowds_doi101007s002650172397y - Visser, Fleur (Dryad Digital Repository, 2017)
PW vocalisation data and associated group-level behaviour data. Data is organised per bin (sampling record). Vocal data is given as seconds recorded in each bin. Database used in binomial and multonomial GEE analysis.